(untitled) (Actualizaciones en Sida e Infectología, 2021)
Introduction: HIV infection is significant in Buenos Aires City. 20% of 5800 new cases/year in the country are from this region. There´s no data about PLwHIV treated in public hospitals of Buenos Aires City about WHO objectives Objetives: To know and analyze the situation PLwHIV treated in public hospitals of Buenos Aires City about treatment, and virological and immunological responses. Methods: Descriptive and retrospective study. Data obtained from the Administration System of HIV Patients actives in June 2018. Variables analyzed: gender, age, ART distribution, VL and CD4 counts, with SPSS 20 Program. Results: 6878 PLwHIV on ART, 66,6% male. 79% with at least 1 VL. Of them, 62% with undetectable VL (78% of all PLwHIV with VL). CD4 data in 56% PLwHIV: 65% >500: In 1st line of TAR 88,3%: 42% boosted IPs, 45% NNRTIs, 13% INIs. Of PLwHIV with undetectable VL, 92% in 1st line of ART (significant). NNRTIs significant for undetectable VL. Discussion: Our cohort represents 50% de los PLwHIV of Buenos Aires City. 62% currently with undetectable VL. NNRTIs still the more used 3rd antiretroviral. High % of PLwHIV on ART without VL and/or CD4 count. Not enough laboratory determinations (VLs and CD4 counts), low data availability and remoteness of WHO´s goals for 2020, show health system´s weakness. Improvements in Access to ART and laboratory determinations and in the data availability and quality are necessary